Animal Industries (De Gruyter, 2024)
This book explores the history and development of animal industries in Nordic countries from their establishment in the late nineteenth century to the present day. It charts the manner in which the value of an animal has primarily come to be understood in commercial terms as a commodity and examines how the scale of this industry threatens the sustainability of the entire planet.